2004
DOI: 10.1007/s00467-004-1511-3
|View full text |Cite
|
Sign up to set email alerts
|

ACE and AT1 receptor gene polymorphisms and renal scarring in urinary bladder dysfunction

Abstract: The objective of this study was to investigate whether DNA polymorphisms of the renin-angiotensin system (RAS) genes were associated with renal scar formation in pediatric patients with bladder dysfunction (BD). Although these children are born healthy, due to persistence of immature voiding habits and evolution of BD, some develop progressive renal damage. It has been suggested that the DD genotype of the angiotensin I-converting enzyme (ACE) gene might be an adverse renal prognostic factor. The insertion/del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
10
0
4
Order By: Relevance
“…Like in many other disease states, genetic polymorphism might be a predisposing factor. However, almost all of the studies investigating the role of RAS gene polymorphisms on renal scar formation related to UTI have been performed in patients with urological abnormality 5,6 , 13,17 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Like in many other disease states, genetic polymorphism might be a predisposing factor. However, almost all of the studies investigating the role of RAS gene polymorphisms on renal scar formation related to UTI have been performed in patients with urological abnormality 5,6 , 13,17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…However, almost all of the studies investigating the role of RAS gene polymorphisms on renal scar formation related to UTI have been performed in patients with urological abnormality. 5,6,13,17,18 Studies investigating the relationship between ACE DD genotype and scar formation in patients with VUR has given contradictory results. Some studies found an association between the ACE DD genotype and renal scar development in patients with VUR, 5,13,18,22 but other studies did not support this association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mizuiri et al [6] reported that the I/D polymorphism affects renal tissue ACE levels and that DD subjects have pronounced renal ACE gene expression. Theoretically, elevated ACE leads to elevated angiotensin II, which promotes proliferation, inflammation, and fibrosis, the main features of renal scarring [18]. Angiotensin II binds to its receptors, AT1 and AT2, and, through the activation of different intracellular signaling pathways, mediates the production of various profibrotic and proinflammatory factors, such as transforming growth factors, cytokines, chemokines, and adhesion molecules [19].…”
Section: Discussionmentioning
confidence: 99%